1999
DOI: 10.1103/physrevstab.2.114202
|View full text |Cite
|
Sign up to set email alerts
|

Space charge dynamics in high intensity rings

Abstract: Uncontrolled beam losses due to space-charge-induced halo generation are a concern in high intensity rings, which are characterized by high beam intensities and low uncontrolled beam loss requirements. It is therefore important to investigate the dynamics of space charge in high intensity rings. We report here the results of extensive calculations using a particle-tracking approach with a self-consistent particle-in-cell model and alternatively with a particle core model. We find that the inclusion of space ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Simulations were carried out with a KV beam for the previous FODO SNS lattice with a working point ͑n x , n y ͒ ͑5.82, 5.77͒ and a space-charge tune shift of about 0.08. We note that in the Appendix we analyze the data based on simulations with the ACCSIM code [1,14]. A detailed comparison of ACCSIM with ORBIT done by Jeon [7] showed that tunes in the vertical direction are slightly less depressed with the ACCSIM code by approximately dn 0.015 compared to the ORBIT code.…”
Section: A Vertical Motionmentioning
confidence: 99%
“…Simulations were carried out with a KV beam for the previous FODO SNS lattice with a working point ͑n x , n y ͒ ͑5.82, 5.77͒ and a space-charge tune shift of about 0.08. We note that in the Appendix we analyze the data based on simulations with the ACCSIM code [1,14]. A detailed comparison of ACCSIM with ORBIT done by Jeon [7] showed that tunes in the vertical direction are slightly less depressed with the ACCSIM code by approximately dn 0.015 compared to the ORBIT code.…”
Section: A Vertical Motionmentioning
confidence: 99%
“…where the parameters 3 τ , 4 τ ,a n d comm τ are 3.3E-6, 3.8E-7, and 2.1E-6 sec, respectively. The first term in the formula (2) describes the time spent binning the macroparticles, applying the space charge kick, etc.…”
Section: Timing Of the Parallel 3d Sc Modelmentioning
confidence: 99%
“…In order to study the dynamics of high intensity rings, a task essential to the SNS project [1], we have developed direct space charge and impedance models in the macro-particle tracking computer code, ORBIT [2,3]. Initially, separate transverse space charge and longitudinal space charge/impedance models were developed, benchmarked, and applied to a number of problems [4,5]. We have now extended the impedance model to include the calculation of forces due to transverse impedances and, because such forces depend on the longitudinal variation of the beam dipole moments, the space charge model has been extended to three dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, these studies were performed for linac beams, where the peak density of particles is much greater than in rings. The effect of space charge on the synchrotron beam is a more recent concern, and analogous PCM studies are being undertaken for the ring beam environment [7]. In these studies, the particle core model has either been applied to idealized lattice structures and beam parameters, or the effects of the lattice have not been critically examined.…”
Section: Introductionmentioning
confidence: 99%